BEYOND THE LOGIC OF POLITICAL ISLAMIC THREAT IN THE WORLD POLITICS - Hasbi Aswar (The Indonesian Islamic Studies and International Relations Association (Insiera), 2017)
This paper aims to discuss the underlying assumption of Western people in discussing the issue of political Islam in world Politics. This issue is analyzed using post-colonial approach in International Relations. This perspective rejects many claims of Western scientific approach on universality and objectivity of the truth or knowledge. Post-colonial approach believes that the process in producing knowledge must have relations with power. This article argues that knowledge about Political Islam that produced within Western perspective is not an objective and universal truth rather it is produces or constructed for a specific political interest, namely to have a control and hegemony to other states and societies.